2019
DOI: 10.3390/biom9110708
|View full text |Cite
|
Sign up to set email alerts
|

Algae: Critical Sources of Very Long-Chain Polyunsaturated Fatty Acids

Abstract: Polyunsaturated fatty acids (PUFAs), which are divided into n-3 and n-6 classes, are essential for good health in humans and many animals. They are metabolised to lipid mediators, such as eicosanoids, resolvins and protectins. Increasing interest has been paid to the 20 or 22 carbon very long chain PUFAs, since these compounds can be used to form lipid mediators and, thus, avoid inefficient formation of dietary plant PUFAs. The ultimate sources of very long chain PUFAs are algae, which are consumed by fish and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 127 publications
(211 reference statements)
1
69
0
Order By: Relevance
“…Our study showed that spray-dried NG produced under controlled culture conditions using UMA 5 culture medium is an important source of ash (21.26%), sodium (5.40%), and calcium (4.11%), and a major source of the polyunsaturated fatty acid EPA (26.73% expressed as a percent of total fatty acids). The high EPA values and the absence of DHA obtained with NG treatment are consistent with the values of these fatty acids reported previously for Nannochloropsis gaditana [ 31 ]. NG concentrate showed no presence of vitamin D 3 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study showed that spray-dried NG produced under controlled culture conditions using UMA 5 culture medium is an important source of ash (21.26%), sodium (5.40%), and calcium (4.11%), and a major source of the polyunsaturated fatty acid EPA (26.73% expressed as a percent of total fatty acids). The high EPA values and the absence of DHA obtained with NG treatment are consistent with the values of these fatty acids reported previously for Nannochloropsis gaditana [ 31 ]. NG concentrate showed no presence of vitamin D 3 .…”
Section: Discussionsupporting
confidence: 91%
“…Microalgae in the aquatic and marine environments are the primary producers of n-3 LC-PUFAs [ 30 , 31 , 32 ]. Microalgae, owing to their composition and simplicity of cultivation, have great potential in the trend of using natural additives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALA is found in green leafy vegetables, flaxseed, walnuts, soybean, and canola oils. Their derivatives, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are obtained through breast milk and the fish oils, such as salmon, mackerel, sardines, anchovies, herring, and rainbow trout, but also algae [7][8][9][10]. Cold-water marine (wild) fishes are abundant in ω-3 PUFAs, since most of them feed on phytoplankton and zooplankton, a rich ω-3 PUFA source.…”
Section: Sources Of Pufasmentioning
confidence: 99%
“…In addition some evidence suggest that longterm supplementation of EPA and DHA may have side effects such as increasing risk of certain types of cancers, but the results are conflicting (Gerber, 2012;Alexander, 2013;Serini and Calviello, 2018). It should be also noticed that the usage of algae-or plant-based sources of EPA and DHA seems more preferable than marine or animal-based sources (Doughman et al, 2007;Lane et al, 2014;Harwood, 2019).…”
mentioning
confidence: 99%